2019
DOI: 10.21500/20112084.4058
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style Classification Questionnaire for latency age: Psychometrics properties of Argentine Sample

Abstract: The purpose of this article was to perform a psychometric study of the Attachment Style Classification Questionnaire (ASCQ) in Spanish language. This paper included three studies. The objectives of study 1 were to analyze the discriminative power of items, to carry out an EFA to determine the structure of the questionnaire, and to calculate the internal consistency of factors. The objectives of study 2 were to test the questionnaire structure through a CFA, and to determine if the model obtained was invariant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
3
0
5
Order By: Relevance
“…El Empathy Quotient (EQ; Baron-Cohen &Wheelwright,2004 ) Continuous from 1 to 5 Transversal De Sancti 2020 Argentina 302 children, (110 male and 128 female) 9-12 yearsold Secure, Anxious and Avoidant Secure, avoidant and ambivalent Significant positive correlation for secure attachment. No correlation for avoidant and ambivalent attachment Attachment Style Classification Questionnaire for Latency Age Children ASCQ ( Finzi Dottan, 2012 ) Continous from 1 to 4 Perspective taking, Emotional Contagion Empathy Questionnaire for children ( Richaud et al, 2019 Continuous from 1 to 5 Transversal Delhaye 2013 Belgium 152 adolescents, (77 female and 75 male) 14.7-18.8 years old Secure-Anxious and Avoidant Secure, avoidant and ambivalent No correlation for secure and ambivalent attachment. Significant negative correlation for avoidant attachment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…El Empathy Quotient (EQ; Baron-Cohen &Wheelwright,2004 ) Continuous from 1 to 5 Transversal De Sancti 2020 Argentina 302 children, (110 male and 128 female) 9-12 yearsold Secure, Anxious and Avoidant Secure, avoidant and ambivalent Significant positive correlation for secure attachment. No correlation for avoidant and ambivalent attachment Attachment Style Classification Questionnaire for Latency Age Children ASCQ ( Finzi Dottan, 2012 ) Continous from 1 to 4 Perspective taking, Emotional Contagion Empathy Questionnaire for children ( Richaud et al, 2019 Continuous from 1 to 5 Transversal Delhaye 2013 Belgium 152 adolescents, (77 female and 75 male) 14.7-18.8 years old Secure-Anxious and Avoidant Secure, avoidant and ambivalent No correlation for secure and ambivalent attachment. Significant negative correlation for avoidant attachment.…”
Section: Methodsmentioning
confidence: 99%
“… Attachment Style Classification Questionnaire for. Latency Age Children ASCQ ( Finzi Dottan, 2012 ) Continous from 1 to 4 Perspective taking, Emotional Contagion Empathy Questionnaire for children ( Richaud et al, 2019 ) Continuous from 1 to 5 Transversal Robinson 2015 Canada Pretest Study: 1205 residents(471 females and 464 males) 32 years old average Anxious and Avoidant Avoidant and ambivalent Significant negative correlation for avoidant attachment. No correlation for ambivalent attachment.…”
Section: Methodsmentioning
confidence: 99%
“…Para evaluar el apego se empleó una adaptación argentina (Richaud et al, 2019) del Attachment Style Classification Questionnaire (ascq) (Finzi et al, 1996). Se trata de un instrumento de autorreporte que puede aplicarse a niños desde los 7 años de edad, e incluye 12 ítems con cinco opciones de respuesta (desde "Para nada verdadero" hasta "Muy verdadero").…”
Section: Instrumentosunclassified
“…Se trata de un instrumento de autorreporte que puede aplicarse a niños desde los 7 años de edad, e incluye 12 ítems con cinco opciones de respuesta (desde "Para nada verdadero" hasta "Muy verdadero"). Los ítems se agrupan factorialmente en tres dimensiones: apego seguro (4 ítems; ω = .73), apego ansioso/ambivalente (4 ítems; ω = .87) y apego evitativo (4 ítems; ω = .71) (Richaud et al, 2019). En el presente estudio, los valores de consistencia interna resultaron aceptables para las tres dimensiones (ω = .69; ω = .67 y ω = .64, respectivamente).…”
Section: Instrumentosunclassified
“…In effect, there is plenty of evidence confirming that empathy plays a very important role in the development of prosociability and its counterpart, aggressiveness, in adolescence. Thus, it has been shown that it is especially related to attachment, prosocial and aggressive behaviors and bullying, among others (see Ang & Goh, 2010;Batanova & Loukas, 2014;Caravita et al, 2009;Espelage & Holt, 2001;Gini et al, 2007;Nickerson et al, 2008;Richaud & Mesurado, 2016;Richaud et al, 2019;Richaud de Minzi, 2013;Van Noorden et al, 2015;Wölfer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%